2014
DOI: 10.1016/j.jbiomech.2014.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Non-uniform displacements within the Achilles tendon observed during passive and eccentric loading

Abstract: The goal of this study was to investigate Achilles tendon tissue displacement patterns under passive and eccentric loading conditions. Nine healthy young adults were positioned prone on an examination table with their foot secured to a rotating footplate aligned with the ankle. Subjects cyclically rotated their ankle over a 25 deg range of motion at 0.5 Hz. An inertial load geared to the footplate induced eccentric plantarflexor contractions with dorsiflexion. Passive cyclic ankle motion was also performed ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
118
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(129 citation statements)
references
References 30 publications
11
118
0
Order By: Relevance
“…A recent study reported that the length of the merged distal portion (∼45% of the total Achilles tendon length) can change from 6.6 to 6.9 mm depending on knee extension and SO+GAS activation (Tijs et al, 2015b; male Wistar rat 315-340 g). Only a few studies have assessed the mechanical response of the SO and LG common tendon in physiological conditions (Finni et al, 1998;Franz et al, 2015;Slane and Thelen, 2014). Interestingly, the consistent finding that the Achilles tendon fascicles in series with the SO or LG undergo differential displacements was interpreted rather differently (Arndt et al, 1999;Bojsen-Møller and Magnusson, 2015).…”
Section: The Role Of the Common Achilles Tendonmentioning
confidence: 99%
“…A recent study reported that the length of the merged distal portion (∼45% of the total Achilles tendon length) can change from 6.6 to 6.9 mm depending on knee extension and SO+GAS activation (Tijs et al, 2015b; male Wistar rat 315-340 g). Only a few studies have assessed the mechanical response of the SO and LG common tendon in physiological conditions (Finni et al, 1998;Franz et al, 2015;Slane and Thelen, 2014). Interestingly, the consistent finding that the Achilles tendon fascicles in series with the SO or LG undergo differential displacements was interpreted rather differently (Arndt et al, 1999;Bojsen-Møller and Magnusson, 2015).…”
Section: The Role Of the Common Achilles Tendonmentioning
confidence: 99%
“…For example, varying knee flexion can elicit differential displacements of the soleus and gastrocnemius aponeuroses [19]. Similarly, our research group showed that knee flexion modulates the uniformity of AT tissue displacements [9]. In addition, Haraldsson et al [20] found negligible inter-fascicle force transmission within the AT and suggested that sliding may allow AT fascicles to act as functionally independent structures.…”
Section: Introductionmentioning
confidence: 95%
“…The free AT (i.e., calcaneus to soleus muscle-tendon junction) consists of distinct fascicle bundles arising from the triceps surae muscles; superficial fascicles arise from the medial gastrocnemius and deeper fascicles arise from the soleus and lateral gastrocnemius [7]. This unique anatomy gives rise to relative motion between fascicle bundles of the free AT [8, 9]. However, the relevance of such non-uniform AT deformations to biomechanical function remains unclear, particularly for tasks such as walking which involve complex coordination between these plantarflexor muscles [10-13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results could therefore represent evidence of altered biaxial strain of the free tendon, during muscle contraction, in response to acute exercise. These changes were not explained by post-exercise differences in muscle activation patterns or torque production, but could reflect non-uniform fatigue or creep of Achilles tendon fascicles, due to differences in mechanical properties and/or tensile loading during eccentric heel drop (Arndt et al, 2011(Arndt et al, , 1998Slane and Thelen, 2014). Irrespective of the cause, acute alterations in the normal biaxial strain could have implications for intra-tendinous force distribution (Haraldsson et al, 2008), fluid flow (Reese et al, 2010;Yin and Elliott, 2004) and tissue homeostasis (Smith et al, 2013) and are therefore relevant in the context of exercise-dependent regional adaptation of Achilles free tendon structure and function.…”
mentioning
confidence: 98%